An Analysis of Arabic Language Learning Problems in Madrasah Aliyah and Their Solutions - Syifa Nazhifah; Isop Syafe'i (Pusaka Cendekia Indonesia Foundation, 2025)
Arabic language learning in Madrasah Aliyah plays a strategic role in developing students’ linguistic competence and Islamic understanding. However, in practice, Arabic language instruction still faces various problems that hinder the optimal achievement of learning objectives. This study aims to examine the problems of Arabic language learning in Madrasah Aliyah, their impacts, and the efforts that can be undertaken to improve the quality of instruction. This research employs a qualitative approach using a library research design. Data were obtained from accredited journal articles, books, theses, and other relevant scholarly sources, and were analyzed using content analysis techniques. The findings indicate that the problems in Arabic language learning include low student motivation and literacy, limited pedagogical competence of teachers, an overloaded curriculum, insufficient learning facilities and media, and the lack of authentic assessment. These problems have an impact on students’ low communicative language proficiency and the ineffectiveness of the learning process. Efforts to address these problems include reorienting learning approaches toward communicative and contextual methods, enhancing teachers’ competencies, strengthening Arabic literacy, optimizing learning media, creating a conducive language environment, and implementing an authentic assessment system. This study is expected to serve as a reference for teachers, madrasahs, and policymakers in improving Arabic language learning in Madrasah Aliyah. Pembelajaran bahasa Arab di Madrasah Aliyah memiliki peran strategis dalam mengembangkan kompetensi kebahasaan dan pemahaman keislaman peserta didik. Namun, dalam praktiknya, pembelajaran bahasa Arab masih menghadapi berbagai permasalahan yang menghambat tercapainya tujuan pembelajaran secara optimal. Penelitian ini bertujuan untuk mengkaji permasalahan pembelajaran bahasa Arab di Madrasah Aliyah, dampaknya, serta upaya-upaya yang dapat dilakukan untuk meningkatkan kualitas pembelajaran. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi pustaka. Data diperoleh dari artikel jurnal terakreditasi, buku, tesis, dan sumber ilmiah relevan lainnya, kemudian dianalisis menggunakan teknik analisis isi. Hasil penelitian menunjukkan bahwa permasalahan dalam pembelajaran bahasa Arab meliputi rendahnya motivasi dan literasi peserta didik, keterbatasan kompetensi pedagogik guru, kurikulum yang terlalu padat, keterbatasan sarana dan media pembelajaran, serta belum optimalnya penerapan penilaian autentik. Permasalahan tersebut berdampak pada rendahnya kemampuan komunikatif bahasa Arab peserta didik dan tidak efektifnya proses pembelajaran. Upaya yang dapat dilakukan untuk mengatasi permasalahan tersebut antara lain dengan mengorientasikan kembali pendekatan pembelajaran ke arah metode komunikatif dan kontekstual, meningkatkan kompetensi guru, memperkuat literasi bahasa Arab, mengoptimalkan penggunaan media pembelajaran, menciptakan lingkungan bahasa yang kondusif, serta menerapkan sistem penilaian autentik. Penelitian ini diharapkan dapat menjadi rujukan bagi guru, madrasah, dan pengambil kebijakan dalam upaya meningkatkan kualitas pembelajaran bahasa Arab di Madrasah Aliyah.